THE EFFECT OF BODY DISSATISFACTION ON DISORDERED EATING ATTITUDES: THE MEDIATING ROLE OF NEGATIVE AFFECTS IN ADOLESCENTS - Zainab, Wajeha; Ahmed, Shoaib; Kumar, Anil; Ali, Shafaq (Journal of Pakistan Psychiatric Society, 2023)
Body dissatisfaction is considered as the most primitive risk factor for developing eating disturbances. Despite the fact that body dissatisfaction is also found in normative population as well, making sense out of it this study aimed to determined the interacting variables which possibly influence the relationship between body dissatisfaction and eating pathology. The study aimed to explored the following mediators: social anxiety and depression and the effects they had on disturbed eating attitudes  among individuals with body dissatisfaction. A total of 300 students were approached aged 15-20 years (mean age = 17.23 years, SD = 1.42 years) who completed the Body Area Satisfaction Subscale of the Multidimensional Body-Self Relations Questionnaire–Appearance Scales, Social Anxiety subscale of self consciousness scale, Patient Health Questionnaire-9  and  Eating, Attitudes Test-26. Based on the research findings, the serial-multiple mediation of social anxiety and depression in the relationship between body dissatisfaction and disturbed eating attitudes was found to be statistically significant. Study findings highlights how body dissatisfaction and eating pathology are linked and what the fundamental mediators are in the chain. Adolescents with disturbed eating, along with the body image issues fear of negative evaluation and negative affects should also acknowledged by the mental health practitioner in order to design effective treatment plans.